Brown Planthoppers Infestations and Insecticides Use Pattern in Java, Indonesia - Hermanu Triwidodo (AGRIVITA, Journal of Agricultural Science, 2020)
In Brown Planthopper (BPH) has caused losses of rice production in Java due to excessive use of pesticides. This research aims to determine the relationship between crop damages caused by BPH and insecticides use schemes. The pesticide use schemes by farmers were observed in 15 districts on Java which were reported for having severe BPH attacks i.e. Banyuwangi, Jember, Blitar, Kediri, Lamongan, Tuban, Bojonegoro, Pati, Demak, Pekalongan, Tegal, Klaten, Sukoharjo and Indramayu, Subang. Most of the sample plots in 15 districts were in the category of damage levels 2 and 3. Most of districts having rice plantations were affected by BPH with insecticides. Rice plants that have the highest level of damage are those with over-pesticide application. There is a significant influence between insecticide use schemes and BPH attack rates in the field. BPH attacks increase in line with the increased use of pesticides, in terms of application frequency, the various types of pesticides, and the number of sprayed mixture pesticides. Many farmers use pesticides that are prohibited for rice cultivation, such as the Pyrethroid and Organophosphate groups. However, the incidence of BPH attacks stilloccur even though there are differences in the pesticide status of legality